Differentiating the Effects of Familial Risk for Alcohol Dependence and Prenatal Exposure to Alcohol on Offspring Brain Morphology. (13th January 2017) - Sharma, Vinod K.; Hill, Shirley Y.
Abstract : Background: Offspring with a family history of alcohol dependence (AD) have been shown to have altered structural and functional integrity of corticolimbic brain structures. Similarly, prenatal exposure to alcohol is associated with a variety of structural and functional brain changes. The goal of this study was to differentiate the brain gray matter volumetric differences associated with familial risk and prenatal exposure to alcohol among offspring while controlling for lifetime personal exposures to alcohol and drugs. Methods: A total of 52 high‐risk (HR) offspring from maternal multiplex families with a high proportion of AD were studied along with 55 low‐risk (LR) offspring. Voxel‐based morphometric analysis was performed using statistical parametric mapping (SPM8) software using 3T structural images from these offspring to identify gray matter volume differences associated with familial risk and prenatal exposure. Results: Significant familial risk group differences were seen with HR males showing reduced volume of the left inferior temporal, left fusiform, and left and right insula regions relative to LR males, controlling for prenatal exposure to alcohol drugs and cigarettes. HR females showed a reduction in the right fusiform but also showed a reduction in volume in portions of the cerebellum (left crus I and left lobe 8). Prenatal alcohol exposure effects, assessed within the familial HR group, was associated with reduced right middle cingulum and left middle temporal volume. Even low exposure resulting from mothers drinking in amounts less than the median of those who drank (53 drinks or less over the course of the pregnancy) showed a reduction in volume in the right anterior cingulum and in the left cerebellum (lobes 4 and 5). Conclusions: Familial risk for AD and prenatal exposure to alcohol and other drugs show independent effects on brain morphology.